Paraparesis and Bipolar Affective Disorder Episodes of Depression in Graves’ Patient with Thyroid Cancer - Yohana Prima Ceria Anindita; Zaki Mita Kusumaadhi; Tania Tedjo Minuljo; K. Heri Nugroho HS; Suryadi; Alifiati Fitrikasari; Subiyakto; Dik Puspasari (PP PERKENI, 2024)
Thyroid nodules in Graves' disease raise awareness of thyroid cancer. Thyrotoxicosis in patients with thyroid cancer suggests extensive metastases or large tumours. Hyperthyroidism or thyrotoxicosis can exacerbate symptoms of anxiety, depression, mood lability, and insomnia in patients with bipolar disorder. We present a rare case, a 29-year-old woman with a history of Graves' variant nodule and bipolar affective disorder since the age of 17, was admitted to the hospital for paraparesis within a month. Patients also complain of sleeplessness, hopelessness, and fatigue. The patient has been taking Thiamazole 10 mg twice daily, Propranolol 20 mg twice daily, Alprazolam 0.5 mg trice daily, Haloperidol 5 mg nightly, Trihexyphenidyl 2 mg daily, Lamotrigine 100 mg twice daily but not routinely. History of partial thyroidectomy 10 years ago with pathology results was said to be benign. Neurological examination: bilateral lower extremity motor weakness with a value of 2/5 muscle function. MRI of the spine with contrast: changes in signal intensity in the vertebral bodies C.2, C.4, C.5, Th.2 - tend to bone metastases. Thyrotoxicosis thyroid function test results (free T4 = 66.71 pmol/L (N = 10.6 – 19.4); TSHs < 0.05 uIU/mL (0.51 – 4.94 uIU/mL) and thyroid scintigraphy showed toxic multinodular goiter (cold nodule) with high thyroid uptake. A total thyroidectomy was performed, and the pathology result revealed papillary thyroid cancer. Thyroid cancer can occur together with Graves' disease. Graves’ disease-associated cancers were more often metastatic to distant sites such as spinal metastases that significantly increases morbidity and mortality. Thyrotoxicosis was associated with regional metabolic changes of limbic structures that mediate affect in patients with bipolar affective disorder.